Issues of Translation of Domestic Service Terms: Focus on Translation Methods (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article addresses the challenges of translating culturally specific domestic service terms from Uzbek into other languages, focusing on the complexities related to cultural nuances and embedded meanings. The study explores different translation methods, including literal translation, adaptation, explicative translation, and functionalist approaches, to evaluate their effectiveness in maintaining cultural integrity. The findings suggest that adaptation and explicative translation are superior methods for conveying cultural meaning and emotional context, while literal translation often fails to capture the depth of cultural significance.